2016
DOI: 10.5194/bg-13-597-2016
|View full text |Cite
|
Sign up to set email alerts
|

Methane dynamics in the subarctic tundra: combining stable isotope analyses, plot- and ecosystem-scale flux measurements

Abstract: Abstract. Methane (CH 4 ) fluxes were investigated in a subarctic Russian tundra site in a multi-approach study combining plot-scale data, ecosystem-scale eddy covariance (EC) measurements, and a fine-resolution land cover classification scheme for regional upscaling. The flux data as measured by the two independent techniques resulted in a seasonal (May-October 2008) cumulative CH 4 emission of 2.4 (EC) and 3.7 g CH 4 m −2 (manual chambers) for the source area representative of the footprint of the EC instrum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 50 publications
3
54
1
Order By: Relevance
“…The effect of LAI TOT on methane flux was about one-third higher than the effect of LAI AER . Previously, Marushchak et al (2016) have found a positive correlation between LAI of vascular plants and methane emissions that explained most of the differences in methane fluxes among the fens and willow stands they measured. The positive effect of LAI TOT on methane flux can be explained by the fact that it provides organic substrate for methanogenesis (Chanton et al, 1995).…”
Section: Discussionmentioning
confidence: 83%
“…The effect of LAI TOT on methane flux was about one-third higher than the effect of LAI AER . Previously, Marushchak et al (2016) have found a positive correlation between LAI of vascular plants and methane emissions that explained most of the differences in methane fluxes among the fens and willow stands they measured. The positive effect of LAI TOT on methane flux can be explained by the fact that it provides organic substrate for methanogenesis (Chanton et al, 1995).…”
Section: Discussionmentioning
confidence: 83%
“…However, there was not a 1:1 relationship between upscaled fluxes using the footprint model and the EC towers, indicating that this methodology may underestimate the overall flux, the opposite to Budischev et al [30], who showed the footprint model method produced a slight overestimation of the flux in comparison to the EC towers, attributed to localised differences in environmental conditions across the measurement period and vegetation classification error. Maruschak et al [90] also upscaled chamber measurements aross a sub-arctic tundra ecosystem, using a high-resolution vegetation map and weighting the fluxes by their relative area. They found that this method again indicated an overestimation of the chamber measurements in comparison to the EC towers.…”
Section: Upscaled Flux Chamber Measurementsmentioning
confidence: 99%
“…Bousquet et al, 2011;Berchet et al, 2015) or data-driven upscaling of eddycovariance-or chamber-based observations (e.g. Christensen et al, 1995;Marushchak et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the assumptions concerning fluxes during winter time or plant transport, according to recent findings (Zona et al, 2016;Marushchak et al, 2016), the settings chosen within the context of this work might be oversimplifying the actual processes in the field. The implemented mechanism that prevents gas exchange with the atmosphere once the snow cover reaches a depth of 5 cm is a very crude approximation of the snow cover influence.…”
Section: Discussionmentioning
confidence: 99%